2014
DOI: 10.1002/ijc.29036
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis smoking and lung cancer risk: Pooled analysis in the International Lung Cancer Consortium

Abstract: To investigate the association between cannabis smoking and lung cancer risk, data on 2,159 lung cancer cases and 2,985 controls were pooled from 6 case-control studies in the US, Canada, UK, and New Zealand within the International Lung Cancer Consortium. Study-specific associations between cannabis smoking and lung cancer were estimated using unconditional logistic regression adjusting for sociodemographic factors, tobacco smoking status and pack-years; odds-ratio estimates were pooled using random effects m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 37 publications
0
87
0
3
Order By: Relevance
“…1 A 2015 article that pooled results of several studies within the International Lung Cancer Consortium found little evidence of increased risk of lung cancer among habitual or long-term marijuana smokers. 4 However, the authors noted that there were considerable flaws in the few studies conducted to date and that "the possibility of potential adverse effect for heavy consumption cannot be excluded." 4 Marijuana smoking has been reported to increase the risk of respiratory problems, such as inflammation of the large airways, increased airway resistance, lung hyperinflation and symptoms of chronic bronchitis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 A 2015 article that pooled results of several studies within the International Lung Cancer Consortium found little evidence of increased risk of lung cancer among habitual or long-term marijuana smokers. 4 However, the authors noted that there were considerable flaws in the few studies conducted to date and that "the possibility of potential adverse effect for heavy consumption cannot be excluded." 4 Marijuana smoking has been reported to increase the risk of respiratory problems, such as inflammation of the large airways, increased airway resistance, lung hyperinflation and symptoms of chronic bronchitis.…”
mentioning
confidence: 99%
“…4 However, the authors noted that there were considerable flaws in the few studies conducted to date and that "the possibility of potential adverse effect for heavy consumption cannot be excluded." 4 Marijuana smoking has been reported to increase the risk of respiratory problems, such as inflammation of the large airways, increased airway resistance, lung hyperinflation and symptoms of chronic bronchitis. 5 Respiratory infections and pneumonia have also been reported at increased rates by marijuana smokers, 3 which suggests that marijuana smoke may compromise the immunologic competence of the respiratory system.…”
mentioning
confidence: 99%
“…Lung cancer risk remains a question. A recent pooled analysis of over 2000 lung cancer cases reported an overall OR for habitual versus nonhabitual or never users as 0.96 (95% CI: 0.66-1.38), and an OR of 1.73 (95% CI: 0.75-4.00) for adenocarcinoma 13 . However, in a 40-year prospective study of 50,000 men, even moderate marijuana use, measured as more than 50 times as a young adult, is associated with a 2-fold increased risk of lung cancer, with persistence of risk when controlled for tobacco and alcohol use and socioeconomic status 14 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Symptoms referable to chronic bronchitis, including daily cough, phlegm production, and wheeze, have been noted in cannabis smokers aft er lessintense use. 9,11,12,15 In terms of lung cancer, epidemiologic data suggesting an association between increased duration and quantity of cannabis exposure with higher odds of lung malignancy development [16][17][18] have not been consistent 19 ( Table 2 ). Together, these epidemiologic data imply that modest consumption of cannabis may have a minimal impact on lung health.…”
Section: Epidemiologic Investigations Related To Cannabis and Lung Hementioning
confidence: 99%